Comparison analysis of childhood body mass index cut-offs in predicting adulthood carotid intima media thickness: Tehran lipid and glucose study - Farhad Hosseinpanah (BMC, 2021)
Abstract Background The prevalence of obesity among children and adolescences have been increased, which can consequently increase the prevalence of metabolic and cardiovascular diseases later in life. The objective of this study is to compare the ability of different childhood body mass index cut-offs in prediction of carotid intima media thickness (CIMT) as an indicator of subclinical atherosclerosis. Methods Participants were categorized into normal weight, overweight and obesity group, based on world health organization (WHO), center for disease control and prevention (CDC), international obesity task force (IOTF) and local IOTF cut-offs. After 18 years of follow up CIMT was measured. Akaike’s information criterion and relative efficiency were measured in order to compare regression models on the role of obesity on CIMT. Results In this prospective cohort study, 1295 subjects aged 3 to 18 years old were enrolled. The overall prevalence of overweight was 15.4, 11.5, 16.3 and 14.1 along with obesity prevalence of 6.6, 8.5, 7.7 and 5.0% based on WHO, CDC, local IOTF and international IOTF criteria, respectively. CIMT was higher in obese compare to normal groups across all classification criteria. After regression analysis, international IOTF was the best to predict adulthood CIMT, followed by local IOTF and WHO. CDC had the least discriminatory ability. Conclusion Due to the results of this study, IOTF could be a better tool in national and international surveillances of children in order to define overweight and obesity, which can help us to intervene more effectively in reducing the burden of cardiovascular diseases.